Analisis Kemampuan Akademik dan Aktivitas Fisik Pengguna Gadget Berlebihan di Kabupaten Rancakalong - Jilan Nur Fajar; Tatang Muhtar; Muhammad Nur Alif; Anggi Setia Lengkana (Tadulako Journal Sport Sciences And Physical Education, 2026)
Excessive gadget use among elementary school students is a growing educational and health concern because it can disrupt the balance between academic learning, physical activity, and social-emotional development. This study analyzed the academic ability and physical activity of excessive gadget users in several elementary schools in Rancakalong District using a convergent parallel mixed-methods design guided by the PRECEDE-PROCEED framework. Quantitative data were obtained from an academic ability test, a Likert-scale screening instrument, and the International Physical Activity Questionnaire-Short Form (IPAQ-SF), whereas qualitative data were collected through observations and interviews with students, parents, and teachers. The quantitative sample consisted of 52 students in grades IV, V, and VI, and six students were purposively selected for in-depth IPAQ-SF and qualitative analysis. The mean academic score was 8.33 out of 20 and was significantly below the minimum competency standard of 12 (t(51) = -11.36; p < 0.001); only four students (7.69%) reached proficiency. IPAQ-SF results showed 5 participants (83.3%) in the moderate physical activity category and 1 participant (16.7%) in the low category, but sitting time remained high at 3-7 hours per day. Qualitative findings explained this active-sedentary paradox through concentration problems, physical discomfort, instant gratification, inconsistent parental mediation, and school-level regulation. The study suggests that excessive gadget use is associated with low academic achievement and unbalanced daily patterns, requiring integrated digital literacy, active learning, parental mediation, and school-based physical activity interventions.